Rural Information Systems: Encourage Participatory Development Towards - Wahda, Muhammad Aksha (Department of Sociology, Universitas Nasional (Indonesia), 2020)
ABSTRACT Measured and precise planning can not be separated from good quality data information. UU No. 6 of 2014 concerning Villages grants the right to villages to create village information systems as a reference in implementing rural development. Village information system is a data storage and processing device consisting of hardware and software. The development of technology that has entered the 4.0 era is a challenge in the innovation of data and information management. The village information system was created by integrating technology 4.0 which facilitates the management and ease of access to data and information. Village information system preparation is carried out in a participatory manner involving all components of the community. So as to produce data and information with good quality. Village information systems are expected to drive progress in rural development by optimizing village potential. Keywords: Village Information System, Village Law, Participatory